Fysisk aktivitet i byens grønne områder - Schipperijn, Jasper; Lindberg, Michael (Forum for Idræt, 2013)
Physical activity in urban green space Physical inactivity is related to several major health problems and 35.1% of Danish adults can be considered inactive. Provision of urban green space is one of the structural factors that is thought to play a role in promoting physical activity. By means of a literature review and an observational case study in two newly renovated urban green space, this study looked at the evidence for a relation between urban green space and physical activity, and more specific, if there are certain elements within urban green space that can promote physical activity. We found that the design of urban green space is related to how the areas are used, by whom, and how active. For individual physical activity, presence of good trails is important whereas areas for play and interaction are most used for group physical activity. Area with a variety of different green space elements located close to each other were very popular among users of our case study areas.